Public Good Theory and the 'Added Value' of the EU's Counterterrorism Policy - Raphael Bossong (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper develops a deductive theoretical framework for assessing the EU's added value in the fight against terrorism. The first part argues that public good theory helps to conceptualize objectives of international counterterrorism cooperation and the respective role of international organizations. It critically evaluates existing discussions of security cooperation from this theoretical perspective and sets out a typology of policies according to three aggregation technologies (weaker links, summation, better shot), each of which is linked to a specific set of governance challenges. The second part surveys the EU's counterterrorism efforts on this basis. Weaker link issues - such as the protection of the movement of people, goods and capital - and the related problem of mutual assurance have been quite successfully addressed, even if there is increasing uncertainty over the boundaries of cooperation. In contrast, the EU fell short with regard to joint efforts in the fight against terrorism due to the non-excludable nature of benefits, as in the case of foreign policy, or (partial) rivalry of consumption, as in the case of intelligence sharing or disaster response capacities. Finally, the EU increasingly supports better shot initiatives to develop new instruments and technologies to combat terrorism, but is often overtaken by mini-lateral forms of cooperation.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330; counterterrorism; public good theory; international organisations; European Union